2021
DOI: 10.1016/j.celrep.2021.110071
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of human anti-viral immunity shaped by virus, tissue, age, and sex

Abstract: The persistence of anti-viral immunity is essential for protection and exhibits profound heterogeneity across individuals. Here, we elucidate the factors that shape maintenance and function of anti-viral T cell immunity in the body by comprehensive profiling of virus-specific T cells across blood, lymphoid organs, and mucosal tissues of organ donors. We use flow cytometry, T cell receptor sequencing, single-cell transcriptomics, and cytokine analysis to profile virus-specific CD8 + T cells recognizing the ubiq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 81 publications
(120 reference statements)
1
38
1
Order By: Relevance
“…SARS-CoV-2 T cell reactivity is influenced by factors such as sex and age [16,17]. As mentioned above, the mild, moderate, and severe disease categories had similar representations of male and female sexes (Figure 1).…”
Section: Sex and Age In Relation To Cd4+ T Cell Responses In Acute Co...mentioning
confidence: 63%
“…SARS-CoV-2 T cell reactivity is influenced by factors such as sex and age [16,17]. As mentioned above, the mild, moderate, and severe disease categories had similar representations of male and female sexes (Figure 1).…”
Section: Sex and Age In Relation To Cd4+ T Cell Responses In Acute Co...mentioning
confidence: 63%
“…Human antiviral immune memory may be influenced by variables such as viral factors related to the infection event such as viral dose and tissue distribution, and host factors such as age, sex, and general health of the host. 126 A distinctive feature of SARS‐CoV‐2 infection and COVID‐19 disease is the wide range of clinical outcomes, ranging from fully asymptomatic infection to severe disease and death. The heterogeneity in clinical outcomes associated with SARS‐CoV‐2 infection and COVID‐19 disease is paralleled by large variations in heterogeneity at the level of CD4 T cell responses.…”
Section: Cd4 T Cell Memory To Sars‐cov ‐2mentioning
confidence: 99%
“…High-dimensional single-cell measurements and fate-mapping techniques have been instrumental in revealing low-frequency but functionally important precursor cells that emerge during the early proliferative period [exemplified by (15)(16)(17)]. Beyond canonical differentiation pathways, single-cell transcriptomic studies of T cells from different anatomical locations, such as (18,19), have demonstrated tissue-associated variation in gene expression within nominal subsets. Thus, T cell differentiation is a highly complex, diverging process.…”
Section: The Branching Tree Of Differentiationmentioning
confidence: 99%